The Implementation of Group Works on English Education Students at the University of Papua: The Perceptions and Problems - Imelda Mallipa (Linguistic, English Education and Art (LEEA) Journal, 2018)
This study aimed at investigating students perceptions on the implementation of group works and the problems that students faced in working with their friends in group. The method of this study was mix method, descriptive quantitave and descriptive qualitative method. The participants were sixty (60) students of the first and second year students in English Education at Papua University. The data for study was taken from a five level Linkert scale questionnaire, open ended questionnaire and students reflection sheet. The results showed that some 30 (50 percent) of students preferred group work to individual work and few students 12 (20 percent) were disagree with group works in their learning proces while some other 18 (30 percent) of students chose no opinion. The problems faced by students were that there were students who were difficult to interact with other tended to be passive in group discussion, those who were hinger achievers tended to dominate in group and did not listen to other opinions (sometimes did not have willingness to study together) then caused students with lower level ability had no confidence to talk in group discussion (sometimes did not come to group discussion), and students who did not want to work had no effort to read and to study materials (only asked for explanation from his or her friends). Thus, it can be concluded that the students in English Education Department at The University of Papua had positive perception on the implementation of group works in teaching process and the problems in working in group came from themselves and from their group members. Key words: group works, the perception, the problems, higher education